Cognitive emotion regulation in unaffected offspring of schizophrenic patients - Kumar, Sudhir; Gaur, Anil; Mohanty, Sandhyarani (International Journal of Research in Medical Sciences, 2017)
Background: Schizophrenic patients are reported to use ‘suppression’ strategy for emotion regulation. Milder levels of psychological issues are observed in first degree relatives of patients with schizophrenia. In this study, we examined usage of cognitive emotion regulation strategies associated with negative emotions in offspring of schizophrenic patients. Method: 20 schizophrenic patients and 20 their offspring were sampled. Cognitive emotion regulation questionnaire and depression, stress, anxiety scales were administered on each participant. Results: The results revealed greater usage of adaptive emotion regulation strategies by offspring and negative strategy by schizophrenic patients. However, under conditions of negative emotions, there is significant reduction in the usage of adaptive coping emotion regulation strategy in the offspring. Conclusion: The results implicate need for strengthening adaptive coping mechanisms under vulnerable conditions of emotional turmoil.